Sp2 C‐Dominant N‐Doped Carbon Sub‐micrometer Spheres with a Tunable Size: A Versatile Platform for Highly Efficient Oxygen‐Reduction Catalysts. (13th December 2012) - Ai, Kelong; Liu, Yanlan; Ruan, Changping; Lu, Lehui; Lu, Gaoqing (Max)
<x xml:space="preserve">Abstract</x> A simple, yet versatile strategy to prepare size‐controlled and monodisperse carbon sub‐micrometer spheres is developed based on the biomolecule dopamine. Unlike traditional carbon materials, the resulting carbon sub‐micrometer spheres contain much less sp3 carbon with high‐level electroactive nitrogen. Moreover, metal–carbon hybrid sub‐micrometer spheres can be easily obtained, and show highly promising catalytic properties in the oxygen‐reduction reaction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>